If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 3 = 4x(3x + 4) Reorder the terms: 3 + 11x = 4x(3x + 4) Reorder the terms: 3 + 11x = 4x(4 + 3x) 3 + 11x = (4 * 4x + 3x * 4x) 3 + 11x = (16x + 12x2) Solving 3 + 11x = 16x + 12x2 Solving for variable 'x'. Combine like terms: 11x + -16x = -5x 3 + -5x + -12x2 = 16x + 12x2 + -16x + -12x2 Reorder the terms: 3 + -5x + -12x2 = 16x + -16x + 12x2 + -12x2 Combine like terms: 16x + -16x = 0 3 + -5x + -12x2 = 0 + 12x2 + -12x2 3 + -5x + -12x2 = 12x2 + -12x2 Combine like terms: 12x2 + -12x2 = 0 3 + -5x + -12x2 = 0 Factor a trinomial. (1 + -3x)(3 + 4x) = 0Subproblem 1
Set the factor '(1 + -3x)' equal to zero and attempt to solve: Simplifying 1 + -3x = 0 Solving 1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 0 + -1 -3x = 0 + -1 Combine like terms: 0 + -1 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333Subproblem 2
Set the factor '(3 + 4x)' equal to zero and attempt to solve: Simplifying 3 + 4x = 0 Solving 3 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = 0 + -3 4x = 0 + -3 Combine like terms: 0 + -3 = -3 4x = -3 Divide each side by '4'. x = -0.75 Simplifying x = -0.75Solution
x = {0.3333333333, -0.75}
| -49-7x=9x+17 | | D-8=12 | | 20=3w-1 | | 4k-9k=10j | | 12x(3x-3)-6x(7x-9)= | | 4(2x+3)=7x+4 | | B(b-7)= | | x^2+18x+19=8x-5 | | 4(10d-4)=64 | | x^2+4x+9=6 | | 10(d-4)=60 | | 3x+2x=4x-8 | | 5(3x+3)=30 | | 2(2m-1)=18 | | 5(m-1)=30 | | 3(5a+2)=36 | | 4(2x)-(x+5)= | | 11u-88=3u | | 3(4x-1)=21 | | 0.5(9x+18)=-1.5(5x)-2(3x+4.5) | | 3x^3+26x^2+35x=0 | | 7w=5w+16 | | 3(3y+5)=5y+25 | | graphy=7+10x | | (x-6)(3x+4)=0 | | y=7+10x | | (1/2)(2x-10)=4 | | x^3-3x^2+9x-54=0 | | x^2-4=6 | | 8(y-5)=6-18 | | .20x+.25+9=.21 | | 4-15y=4 |